PERKEMBANGAN PERBANKAN SYARIAH DI INDONESIA - Nofinawati, Nofinawati (Faculty of Shariah of State Institute for Islamic Studies Batusangkar, Indonesia, 2015)
Sharia banking in Indonesia has approached 24 years of age. This age implies that it such sharia banking has shifted to maturity phase. It has developed significantly compared to that of previous years. It can be observed from its average growth of its assets, DPK, PYD which is 45% higher than the years of 2000 up to 2014. However, it is expected that it must able to make use of opportunities which are presently available to encounter challenges in the future, Consequently, it should be able to take advantage of supports and contributions of other such related parties as government, ulama, society, academicians, and students majoring in sharia banking as well. Kata kunci: development, sharia banking, Indonesia